Chinese cognitive processing of ToM: Distinctions in understanding the mental states of self, close others, and strangers - Wang, Yuanqing; Yuan, Xiaojing (Frontiers in Psychology, 2023)
Carried out with the Chinese culture as background, this study reveals whether people use different processing mechanisms when attributing mental states to themselves versus comprehending the mental state of others. A self/other differentiation task was adopted as the research paradigm. It emerged that the time required to reflect on one’s self mental state is shortest in mental state attribution, longer when comprehending the mental state of close others, and longest for strangers. This result indicates that Chinese participants distinguish between close others and strangers when performing perspective-taking. When the perspective-shifting of belief-attribution is performed, a beforehand processing of information about close others or strangers does not interfere with the processing of information from oneself subsequently. However, when information from oneself was processed in the previous stage, it interfered with the processing of information from both close others and strangers in the later stage. This finding indicated that processing the self mental state is automatically activated, but comprehending the mental state of others is not. The comprehension of others’ mental states occurs only when required by the task and it entails more cognitive resources to process and maintain.